Performance characteristics of low carbon waste material to stabilise soil with extremely high plasticity - Ali Al-Baidhani (CTU Central Library, 2021)
The application of low-carbon and natural materials to mitigate the undesired properties of difficult soils is considered as a sustainable solution to the issues regarding these soils. Selecting some natural materials, of low carbon type, from the rubble of demolished buildings or debris from the construction of new buildings and recycling them in a poor or weak soil stabilisation process is a very little explored field of research in Iraq. This paper investigated the geotechnical characteristics of extremely high plasticity soil (EHPS) improved with a low-carbon building stone debris (BSD). Five dosages from coarse and fine soil-size ((BSDC) and (BSDF)) of BSD have been prepared to use in the EHPS-BSD mixtures. The laboratory tests included Atterberg limits, linear shrinkage, unconfined compression, consolidation, and swelling. The effect of the BSD on the time to zero-water content and the maximum swell was included. The efficiency of the BSD was proved by the amelioration of the compressibility and strength, and by reducing the shrinkage, swell pressure, and the potential of swelling. The shrinkage, compressibility, and swelling properties of the EHPS were reduced depending on the gradation and content of BSD. The gradation of BSD had a major role in strength development and controlling the time required to reach the final shrinkage and maximum swell stage.